2011
DOI: 10.1093/bja/aeq360
|View full text |Cite
|
Sign up to set email alerts
|

Information gain in patients using a multimedia website with tailored information on anaesthesia

Abstract: A patient-tailored multimedia website is an effective way to support the information provided by the anaesthesiologist in order to inform patients about their upcoming anaesthetic procedure. The use of such a website gives a significant increase in knowledge compared with only spoken information, or spoken information combined with a brochure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
0
21
0
4
Order By: Relevance
“…Personalized counselling, oral or written, and relaxation techniques may reduce anxiety and fear and improve recovery. Detailed explanations of procedure and specific daily targets for the postoperative period may facilitate eating, mobilization, pain control and respiratory function, thus reducing the risk of complications.…”
Section: Preoperative Counsellingmentioning
confidence: 99%
“…Personalized counselling, oral or written, and relaxation techniques may reduce anxiety and fear and improve recovery. Detailed explanations of procedure and specific daily targets for the postoperative period may facilitate eating, mobilization, pain control and respiratory function, thus reducing the risk of complications.…”
Section: Preoperative Counsellingmentioning
confidence: 99%
“…The amount of medical information available in the internet seems to be sufficient to satisfy most users and to contribute in reducing confusion about their personal medical issues [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…Although it is a standard of care to provide patients with a complete explanation of care, time constraints sometimes hinder the ability to fully do so [4]. This results in patients employing their own methods to obtain information.…”
Section: Introductionmentioning
confidence: 99%
“…A major concern that arises is the comprehensibility of the materials patients may read. Nevertheless, studies have shown that the specific use of a computer website, as opposed to other forms of structured information, before scheduled surgery elicited a greater acquisition of knowledge of preoperative anesthesia [4].…”
Section: Introductionmentioning
confidence: 99%